Exploring the modulatory effects of brown seaweed meal and extracts on intestinal microbiota and morphology of broiler chickens challenged with heat stress - Fisayo Oretomiloye; Deborah Adewole (Poultry Science, 2024)
ABSTRACT: Brown seaweed (Ascophyllum nodosum) is known for its prebiotic roles and can improve animal intestinal health by enhancing the growth of beneficial microbes and inhibiting pathogenic ones. However, the gut health-modulatory roles of brown seaweed on chickens challenged with heat stress (HS) are rarely studied. The current study examined the effects of brown seaweed meal (SWM) and extract (SWE) on the ceca microbiota and small intestinal morphology of chickens challenged or unchallenged with HS. Three hundred and thirty-six 1-day-old Ross 308 broiler chicks were randomly assigned to either a thermoneutral (TN; 24 ± 1°C); or HS room (HS; 32–34°C, 8 h/d from d 21 to 27). All birds in each room were randomly allotted to 4 treatments – control (CON), CON + 1 mL/L seaweed extract (SWE) in drinking water, CON + 2 mL/L SWE in drinking water, and CON + 2% seaweed meal (SWM) in feed and raised for 28 d. On d 14 and 28, 12 and 24 birds per treatment group, respectively, were euthanized to collect the ceca content for gut microbiota analysis and small intestinal tissues for morphological examination. On d 14, 2% SWM increased (P = 0.047) the relative abundance of cecal Fecalibacterium and all brown seaweed treatments improved jejunal villus height (VH) and VH:CD compared to the CON diet. On d 28, HS significantly reduced (P < 0.05) ileal VH, VW, and VH:CD, and duodenal VH and VH:CD. Among the HS group, 2% SWM and 2 mL/L SWE significantly increased (P < 0.05) the relative abundance of Lactobacillus, Sellimonas, and Fournierella, compared to the CON diet. HS birds fed with 2% SWM had higher ileal VH and VH:CD compared to other treatments. In summary, SWM and SWE enhanced the abundance of beneficial microbes and improved small intestinal morphology among HS chickens. This implies that seaweed could potentially alleviate HS-induced intestinal impairment in chickens.